Characteristic, Behaviour, Lung Function of Workers and PM2,5 Concentration in Cecek Home Industry Sidoarjo Regency - Zuhrida Aulia; R. Azizah (Universitas Airlangga, 2015)
Abstract: PM2,5 as one of the air pollutions parameters can be derived from burning wood. Negative impact from PM2,5 exposure on health are impaired lung function. This study was conducted to analyze characteristics, behaviors, lung function of workers and PM2,5 concentration in cecek home industry Katerungan Village, Krian District of Sidoarjo Regency. This research used cross sectional design with total population, 10 workers. Indoor PM2,5 concentration in production area and warehouse space were measured using EPAM 5000 and workers lung function was measured using spirometry test. Individual characteristics and behaviors of workers were analysed using descriptive quantitatively to lung function. Individual characteristics variable consists of age, job tenure, medical history and BMI. Behavioral variables focus on smoking habit. The result of this research showed that PM 2.5 concentration in production area and warehouse space still under the environmental quality standards (< 10 mg/m3). 40% workers in production area and 80% workers in warehouse space got impaired lung function. We can conclude that impaired lung function of workers in cecek home industry Katerungan Village, Krian District of Sidoarjo Regency is not caused of PM2,5 exposure, but job tenure, medical history, BMI, smoking habit for more than 5 years and more than 1 pack per day. Impaired lung function more likely happen to worker with job tenure more than 5 years, having historical respiration disease, having wasted nutritional status and have been smoked more than 5 years and more than 1 pack per day. The suggestion is that workers with impaired lung function should have advanced diagnosis and therapy. For the owner of a home industry, should require his workers wearing masks at work place.Keywords: PM2,5, lung function, cecek home industry